Poster 186: Repair of the Distal Biceps Tendon: A Systematic Review & Network Meta-Analysis of Biomechanical Performance. Issue 7 (30th July 2022) - Lavoie-Gagne, Ophelie; Parvaresh, Kevin; Agarwalla, Avinesh; Forsythe, Brian; Forlenza, Enrico
Objectives: Rupture of the distal biceps is common and demonstrates excellent short- and long-term clinical outcomes following surgical repair. Prior studies have individually evaluated the biomechanical construct strength of multiple fixation devices, but none has comprehensively evaluated constructs in a head-to-head comparison. We sought to compare the failure strength, maximum strength, stiffness and displacement of available constructs for distal biceps repair. Methods: A network meta-analysis was conducted to determine the relative performance of 2 all-suture suture anchors, 2 intramedullary cortical buttons, 2 suture anchors, extramedullary cortical buttons, extramedullary cortical button plus interference screw, interference screw, single intramedullary cortical button, single suture anchor, trans-osseous suture, tension slide technique and tension slide technique plus suture tape. Analysis consisted of arm-based network meta-analysis under Bayesian random-effects model with Markov Chain Monte Carlo (MCMC) sampling. Geometry of the network was represented visually via a network plot with nodes representing treatments and edges representing direct comparative evidence. Biomechanical outcomes of fixation techniques were summarized as treatment effects and their corresponding 95% confidence intervals (CI). Rank probabilities were calculated and used to generate each treatment's surface under the cumulative ranking (SUCRA) curve. Results: A total of 21 studies were included in the network meta-analysis. For failure strength, the two intramedullary cortical buttons ranked highest (92.73%). For maximum strength, the extramedullary cortical button alone (86.96%) and extramedullary button plus interference screw (83.40%) ranked highest. The two intramedullary cortical buttons ranked highest in stiffness (98.75%), followed by the extramedullary cortical button with interference screw (88.75%) and extramedullary cortical button (75.00%). Finally, with respect to demonstrating the least displacement after loading, the two suture anchors (89.43%) ranked highest, followed by tension slide technique with suture tape (73.14%) and extramedullary cortical button (72.71%). Conclusions: The fixation constructs that demonstrated the greatest overall biomechanical performance in distal biceps tendon repair were the extramedullary cortical button and two intramedullary cortical buttons. Two suture anchors demonstrated the least displacement after loading. Figure 1. Cochrane risk of bias summary of included studies. Figure 2. Evidence networks for outcomes of failure strength (A), maximum strength (B), stiffness (C), and displacement (D). The thickness of each line connecting two nodes is proportional to how often these two interventions were compared, while the size of each node is proportional to the respective patient sample size. Figure 3. Forest plot displaying the effect difference of each intervention on (A) failure strength, (B) maximum strength, (c) stiffness, and (D) displacement.